Halal food security: forensic and laboratory management - Jaswir, Irwandi; Mirghani, Mohamed Elwathig Saeed; Almansori, Bubaker Hamad; Octavianti, Fitri (CRC Press, 2019)
The need for proper control and monitoring of authenticity of food is a serious matter to the authority and the food manufacturers. Strong commitment and continuous support from the government through various agencies would ensure the integrity of the food itself, both in terms of safety and quality. People of all faiths have a consensus in consuming food and drink of vegetable origin. In Islam, all things created by God (Allah) are permitted or halal to be eaten, with a few exceptions that are specifically prohibited (haram) which are pork, blood, carrion and animals slaughtered without invoking the name of Allah. Islamic food laws are based on cleanliness, sanitation and purity. All utensils must be clean and free of contamination from any unlawful or harmful substances. Islam does not prohibit vegetable foods, with the exception of what is fermented, either it be grapes, dates, barley, or any other substances, as long as it remains in the unfermented state; similarly, Islam prohibits anything which intoxicates, affects the functioning of the brain, or harms the body (Al-Qaradawi, 1984). However, with regard to foods derived from animal sources, people and nations have held widely varying attitudes. Hence, the importance establishing laboratories and using analytical techniques (methods) of authenticity in food for ensuring food safety and protecting consumers from fraud and deception as well as for product recall purposes. Halal analytical laboratory facilities should fit the purpose and ensure competence personnel and equipment. Laboratory data may help define the overall scope of work, levels of worker protection, as well as remediation and disposal methods. The laboratory information management system should be stated in such away that allows matching analytical results with relevant field data. Instrumental methods in detection of contamination and/or adulterants in food would clarify any doubt to Muslims and information can be disseminated for consumer transparency giving better trust and confidence to the authority. This paper discusses the management of laboratory for halal product analysis with the emphasis of the use of instrumental-based analysis.